2024
DOI: 10.1146/annurev-ento-012323-032231
|View full text |Cite
|
Sign up to set email alerts
|

Emerald Ash Borer Management and Research: Decades of Damage and Still Expanding

Jianghua Sun,
Tuuli-Marjaana Koski,
Jacob D. Wickham
et al.

Abstract: Since the discovery of the ash tree ( Fraxinus spp.) killer emerald ash borer (EAB; Agrilus planipennis) in the United States in 2002 and Moscow, Russia in 2003, substantial detection and management efforts have been applied to contain and monitor its spread and mitigate impacts. Despite these efforts, the pest continues to spread within North America. It has spread to European Russia and Ukraine and is causing sporadic outbreaks in its native range in China. The dynamics of EAB's range expansion events appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…The survival success of a non-indigenous species in establishing itself in a new region is contingent upon favorable climatic conditions [49,50], a sufficient number of host trees [51], and a minimum in competitors or entomophagous [52,53]. Therefore, various approaches to predicting the EAB spread have considered climatic conditions favorable for pest survival and propagation [33,49,54,55], the spread of a host plant [12,56], landscape and stand characteristics [57], the possibility of active adult migration along the roads and the passive spread of larvae with wood chips [32], other trunk fragments with bark, and various combinations [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The survival success of a non-indigenous species in establishing itself in a new region is contingent upon favorable climatic conditions [49,50], a sufficient number of host trees [51], and a minimum in competitors or entomophagous [52,53]. Therefore, various approaches to predicting the EAB spread have considered climatic conditions favorable for pest survival and propagation [33,49,54,55], the spread of a host plant [12,56], landscape and stand characteristics [57], the possibility of active adult migration along the roads and the passive spread of larvae with wood chips [32], other trunk fragments with bark, and various combinations [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that EAB is well-adapted to temperature variations [6]. Particularly in Ukraine, using the MaxEnt model and 19 bioclimatic variables [9] resulted in high accuracy (AUC = 0.988) in predicting EAB invasion for 87% (Luhansk), 48% (Kharkiv), and 32% (Donetsk).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation